Design, synthesis and optimization of bis-amide derivatives as CSF1R inhibitors. Issue 10 (15th May 2017) - Ramachandran, Sreekanth A.; Jadhavar, Pradeep S.; Miglani, Sandeep K.; Singh, Manvendra P.; Kalane, Deepak P.; Agarwal, Anil K.; Sathe, Balaji D.; Mukherjee, Kakoli; Gupta, Ashu; Haldar, Srijan; Raja, Mohd; Singh, Siddhartha; et al.
Graphical abstract: Abstract: Signaling via the receptor tyrosine kinase CSF1R is thought to play an important role in recruitment and differentiation of tumor-associated macrophages (TAMs). TAMs play pro-tumorigenic roles, including the suppression of anti-tumor immune response, promotion of angiogenesis and tumor cell metastasis. Because of the role of this signaling pathway in the tumor microenvironment, several small molecule CSF1R kinase inhibitors are undergoing clinical evaluation for cancer therapy, either as a single agent or in combination with other cancer therapies, including immune checkpoint inhibitors. Herein we describe our lead optimization effort that resulted in the identification of a potent, cellular active and orally bioavailable bis-amide CSF1R inhibitor. Docking and biochemical analysis allowed the removal of a metabolically labile and poorly permeable methyl piperazine group from an early lead compound. Optimization led to improved metabolic stability and Caco2 permeability, which in turn resulted in good oral bioavailability in mice.